Efektivitas Pelayanan Sistem Penerimaan Murid Baru (SPMB) di Sekolah Menengah Pertama Negeri 4 Lamongan - Evanda Arsinta Rahma; Meirinawati M; Eva Hany Fanida; Fitrotun Niswah (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study aims to analyze the effectiveness of the New Student Admission System (Sistem Penerimaan Murid Baru/SPMB) services at SMP Negeri 4 Lamongan in the 2025/2026 academic year. The research employed a qualitative approach with a descriptive design. Data were collected through observations, in-depth interviews, and documentation involving the SPMB committee, prospective students, and parents. The main research instrument was the researcher, supported by interview and observation guidelines. Data analysis was conducted inductively using the Miles and Huberman interactive model, consisting of data collection, data reduction, data display, and conclusion drawing. The results indicate that the implementation of SPMB services at SMP Negeri 4 Lamongan was effective in terms of goal achievement, integration, and adaptation. Admission targets were achieved according to the established capacity, coordination among committee members was well organized, and adaptive measures were implemented to address technical constraints and community needs. However, improvements in technical socialization and assistance are still required to enhance the quality of SPMB services in the future.